Effects of a community-based salt reduction program in a regional Australian population. (December 2016) - Land, Mary-Anne; Wu, Jason; Selwyn, Adriana; Crino, Michelle; Woodward, Mark; Chalmers, John; Webster, Jacqui; Nowson, Caryl; Jeffery, Paul; Smith, Wayne; Flood, Victoria; Neal, Bruce
Abstract Background Salt reduction is a public health priority but there are few studies testing the efficacy of plausible salt reduction programs. Methods A multi-faceted, community-based salt reduction program using the Communication for Behavioral Impact framework was implemented in Lithgow, Australia. Single 24-h urine samples were obtained from 419 individuals at baseline (2011) and from 572 at follow-up (2014). Information about knowledge and behaviors relating to salt was also collected. Results Survey participants were on average 56 years old and 58 % female. Mean salt intake estimated from 24-h urine samples fell from 8.8 g/day (SD = 3.6 g/day) in 2011 to 8.0 (3.6) g/day in 2014 (−0.80, 95 % confidence interval −1.2 to −0.3;p < 0.001). There were significant increases in the proportion of participants that knew the recommended upper limit of salt intake (18 % vs. 29 %;p < 0.001), knew the importance of salt reduction (64 % vs. 78 %;p < 0.001) and reported changing their behaviors to reduce their salt intake by using spices (5 % vs. 28 %;p < 0.001) and avoiding eating out (21 % vs. 34 %;p < 0.001). However, the proportions that checked food labels (30 % vs. 25 %;p = 0.02) fell, as did the numbers avoiding processed foods (44 % vs. 35 %;p = 0.006). Twenty-six percent reported using salt substitute at the end of the intervention period and 90 % had heard about the program. Findings were robust to multivariable adjustment. Conclusions Implementation of this multi-faceted community-based program was associated with a 10 % reduction in salt consumption in an Australian regional town. These findings highlight the potential of well-designed health promotion programs to compliment other population-based strategies to bring about much-needed reductions in salt consumption. Clinical trial registration NCT02105727 .